Das heutige System periodischer Märkte im Kreise Zouping (Shandong/China) - Matzat, Wilhelm (ERDKUNDE, 1993)
In the 1988 volume of this periodical (Erdkunde, Vol. 42) I reported on YANG CHINGKUN'S pioneer study of periodic markets, which he had conducted in 1932/33 in Zouping county and published in mimeographed form in New York 1944. In 1989 and 1991 I visited Zouping county in order to investigate the present system of its periodic markets. YANG'S study served as a basis for an evaluation of changes between 1933 and 1989. It appears that this county is still an economically retarded and conservative area: nearly all the old market-places were revitalized after 1980 and they still have the tradition al rhythm of two market-days per decade. No new market-places were created, some minor markets in the vicinity of the county seat have been closed. Because of population growth the number of visitors and demand density has increased considerably in the higher level markets, where more and more permanent shops are being established. On the other hand it is surprising to see that so many minor markets still exist.